Progress in Vehicle Aerodynamics and Thermal Management 11th FKFS Conference, Stuttgart, September 26-27, 2017 - Wiedemann, Jochen; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
The books presents latest information about new car developments, new or improved testing techniques and new or improved calculation procedures. Presenters are from industry and academia.
Thermal Management -- Cooling Air Flow -- Unsteady Flow -- New Vehicles -- On-Road Tests -- Aerodynamic Development.
Keywords: Automotive engineering; Automotive Engineering